Private information flow and price discovery in the U.S. treasury market - George J. Jiang; Ingrid Lo (Bank of Canada, 2011)
Existing studies show that U.S. Treasury bond price changes are mainly driven by public information shocks, as manifested in macroeconomic news announcements and events. The literature also shows that heterogeneous private information contributes significantly to price discovery for U.S. Treasury securities. In this paper, we use high frequency transaction data for 2-, 5-, and 10-year Treasury notes and employ a Markov switching model to identify intraday private information flow in the U.S. Treasury market. We show that the probability of private information flow (PPIF) identified in our model effectively captures permanent price effects in U.S. Treasury securities. In addition, our results show that public information shocks and heterogeneous private information are the main factors of bond price discovery on announcement days, whereas private information and liquidity shocks play more important roles in bond price variation on non-announcement days. Most interestingly, our results show that the role of heterogeneous private information is more prominent when public information shocks are either high or low. Furthermore, we show that heterogeneous private information flow is followed by low trading volume, low total market depth and hidden depth. The pattern is more pronounced on non-announcement days.
Keywords: G12; G14; 330; Financial markets; Market structure and pricing; Finanzmarkt; Informationsversorgung; Schock; Schatzpapier; Preis; USA